2022
DOI: 10.3390/w14091517
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antibiotic Resistance in Escherichia coli Isolates from Fecal and Water Sources in Laguna Lake, Philippines

Abstract: Due to the misuse and overuse of antibiotics, antibiotic residues accumulate in natural environments, leading to the development of antibiotic-resistant bacteria (ARBs). The presence of ARBs in bodies of water poses health hazards to the surrounding community. This study focused on Laguna Lake, the largest lake in the Philippines, which serves as a water source for agriculture and domestic purposes. We aimed to detect the presence of antibiotic-resistant Escherichia coli from the lake waters and potential rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The current study found that most clinical E. coli isolates were highly resistant to AMP. Our findings corroborate findings from other studies where E. coli isolates from clinical and environmental samples were highly resistant to penicillins such as AMP [ 85 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. The high resistance of E. coli to ampicillin can be attributed to its potential to develop intrinsic resistance against penicillins.…”
Section: Discussionsupporting
confidence: 92%
“…The current study found that most clinical E. coli isolates were highly resistant to AMP. Our findings corroborate findings from other studies where E. coli isolates from clinical and environmental samples were highly resistant to penicillins such as AMP [ 85 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. The high resistance of E. coli to ampicillin can be attributed to its potential to develop intrinsic resistance against penicillins.…”
Section: Discussionsupporting
confidence: 92%
“… 87 Additionally, our findings are consistent with those reported in other studies. 14 , 53 , 60 , 85 , 94 The resistance of E. coli to ampicillin may indicate the misuse of penicillins in the poultry sector. Additionally, studies in humans have also reported high resistance of E. coli to ampicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has unveiled the prevalence of multidrug-resistant (MDR) E. coli in poultry and farm animals, as indicated by some studies ( 17 , 18 ), and highlighted the associated risks of transmission from such sources ( 19 ). Moreover, freshwater bodies across the globe have been found to harbor MDR E. coli bacteria ( 20 22 ). Some studies have even detected such strains in drinking water ( 23 ).…”
Section: Introductionmentioning
confidence: 99%